'There's a lot of places I'd like to go and things I'd like to do': the daily living experiences of adults with mild to moderate intellectual disabilities during a time of personalised social care reform in the United Kingdom. Issue 3 (16th March 2017) - Hamilton, L. G.; Mesa, S.; Hayward, E.; Price, R.; Bright, G.
Abstract: Adult social care services in the United Kingdom have undergone a period of transformation over recent years, characterised by a drive towards personalised care. Concurrently, social care budgets have been significantly reduced. This study aimed to explore the daily living experiences of adults with mild/moderate intellectual disabilities, who are at risk of no longer meeting eligibility criteria for statutory support. Focus group discussions, which included both people with intellectual disabilities and support workers, were analysed thematically. Two broad themes are presented: independence and agency; and social capital and well-being. While some participants echoed ideas central to the personalisation narrative, a number of contextual barriers to achieving greater independence and agency were discussed. Moreover, greater independence was not a desired goal for all participants. The findings highlight the potential mismatch between personalised social care, as delivered within significant budget constraints, and the needs of adults with intellectual disabilities.